Kajian Dampak Reklamasi Pantai Terhadap Perubahan Kondisi Lingkungan Sosial Ekonomi Masyarakat Di Kota Ternate - Adjam, Syarifuddin; Sinyo, Yumima (Universitas Khairun, 2023)
The aim of this research is to determine the impact of beach reclamation on changes in the socio-economic conditions of the community in Ternate City. The type of research is quantitative descriptive. The method used was survey and purposive sampling which was carried out in two locations, namely Kampung Makasar Timur Village and Salero Village. The sample of respondents consisted of 42 people from village heads, traders, hunters, youth and fishermen as well as visitors to tourist areas. Data collection through interviews using questionnaires. The results of the research show that the highest percentage is in the affirmative answer with each indicator percentage, namely (1) Indicator of community perception and attitude towards coastal reclamation development 24%, (2) Indicator of community attitude towards the coastal reclamation environment 71%, (3) Indicator of change patterns of social relations between communities 26%, (4) Indicators of changes in community livelihoods 50% and (5) Indicators of social conditions in the community of respondents who agreed were 62%.